Expression of FoxO3a in sepsis mice and its association with lymphocyte apoptosis: FoxO3a in sepsis mice - Wen, Ya; Li, Yan; Guo, Jinli; Shang, Kaijian (Cellular and Molecular Biology, 2024)
This study investigated forkhead box O3a (FoxO3a) expression in peripheral blood of sepsis mice and its correlation with lymphocyte apoptosis. Sixty male C57 mice were randomly assigned to sham, model, and intervention groups. Sepsis was induced via cecal ligation in the model and intervention groups, while sham mice underwent similar procedures excluding cecal ligation. Apoptosis proteins in lymphocytes were assessed by Western blotting, reactive oxygen species (ROS) levels by 2,7-Dichlorodi-hydrofluorescein diacetate (DCFH-DA), and serum interleukin-1β (IL-1β) and IL-10 content. The model group exhibited elevated mortality, increased lymphocyte apoptosis, higher Caspase3 expression, and lower Bcl-2/Bax ratio compared to sham and intervention groups. Additionally, the model group displayed decreased serum IL-10, elevated IL-1β, heightened lymphocytic ROS, reduced FoxO3a expression, and increased levels of p-FoxO3a, p-PI3K, and p-Akt compared to sham. In sepsis mice, inhibited FoxO3a signaling in lymphocytes leads to enhanced apoptosis, elevated ROS, and immune cell dysfunction, contributing to increased mortality.